(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to provide a comprehensive overview of the concept of the role of strategic leadership in achieving competitive advantage. The study also aims to determine the role of strategic leadership in achieving competitive advantage in Dallah Al Baraka Company - Jeddah, and to know the level of practices of its senior leadership, and to know the level of practices of middle leadership (department heads). of senior leaders and employees from the point of view of their employees. To achieve the objectives of the study in the chosen environment, Dallah Al Baraka Group of Companies - Jeddah, the field study was applied to a sample of (30) of the company’s employees, divided into 10 (senior leadership); (10) Department heads; (10) employees in the departments, and a questionnaire form was designed with a set of scales, and each scale measures each dimension and each variable separately. The questionnaire form included four sections: demographic data, the role of strategic leadership in achieving competitive excellence, and the impact of strategic leadership on financial performance, the impact of strategic leadership on creative and innovative aspects. Then the researcher used the descriptive analytical method through which he attempts to describe the phenomenon - the subject of the study, answer its questions, and test its hypotheses - and analyze its data using the statistical program SPSS. The study reached several results, the most important of which are: Strategic leadership decisions and practices led to an increase in revenues and profits at Dallah Al Baraka Company. Strategic leadership also contributed to achieving growth and expansion in the organization’s activities and investments. The study also demonstrated the presence of clear indicators that reflect the impact of leadership on competitive advantage. The results of the study confirmed that leadership practices work to achieve competitive excellence in a sustainable manner in Dallah Al Baraka companies, and that creativity and encouraging innovation is the primary factor in enhancing the competitive ability of the organization. The study concluded with some recommendations, the most important of which is the necessity of having effective communication channels to achieve the primary goal of strategic leadership, let it be strategic communication. The study also recommended the need to strive towards training the organization’s employees, whether they are leaders or employees in their work sites, in a way that enables them to perform their work and achieve innovative growth during training.